Home advantage in the Brazilian soccer championship: effect of game location and team quality - Silva, Cristiano Diniz da (2010)
The objective of the present study was to evaluate home advantage in Brazilian soccer considering the interference of and interaction between game location and team quality in the percentage of wins and draws. Data from the Brazilian first-division soccer championship comprising a period of 10 years (1998-2007) were analyzed, for a total of 3,836 games. For club qualification the first deviation of the curve of Gauss was used in relation to the punctuation obtained. Clubs presenting a punctuation higher than this deviation were classified as high quality (HQ), clubs with an intermediate punctuation as average quality (AQ), and clubs with a lower puncutation as low quality (LQ). There was an effect of game location (p< 0.001; η2=0.88), with clubs playing at home winninng on average 25% more games. This effect was less pronounced for LQ teams compared to AQ and HQ teams (p< 0.001), a find-ing indicating a significant effect of team quality (η2=0.89). A significant, although of medium strength, interaction was observed between team quality and game location for the percentage of wins at home (p=0.023; η2=0.13). There was also a significant relationship between game location and team quality for draws (p< 0.001; η2=0.39), with no important influence of the individual factors. HQ teams presented fewer draws at home than away, while the opposite was observed for LQ clubs (p< 0.05). No difference between draws at home and away was observed for AQ teams. In conclusion, game location is an advantageous factor in Brazilian first-division soccer championship games, with this factor being more pronounced in the case of high quality teams.